(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background & Objective: Umbilical cord length and number of loops around fetal neck leads to intrapartum complication which can predict by antenatal screening. This study was carried out to find the effect of length of umbilical cord on intrapartum complication, mode of delivery, perinatal outcome. Methods: This is a prospective study conducted at NHL MMC from August 2020 to July 2021. Total 300 cases were taken. Antenatal ultrasound carried out to screen nucle cord and after delivery number of loops were noticed and APGAR score noted. Results: Out of 300 cases 5 case were <35 cm and 2 cases >102 cm ,97 cases were 66-75cm. 86% had medium cord length, 8.67% had long, 5.3% short cord length. 11.5% case with long case had IUFD. 85.7% with 3 loops delivered by cesarean section. Conclusion: Increase umbilical cord length and loop associated with complication like fetal heart rate variation, fetal asphyxia, increase cesarean rate. Intrapartum fetal monitoring avoids perinatal morbidity and mortality.